Potential Applications for Solar Photocatalysis: From Environmental Remediation to Energy Conversion - Machado, Antonio Eduardo Hora; Santos, Lidiaine Maria dos; Borges, Karen Araújo; Batista, Paulo dos Santos; Paiva, Vinicius Alexandre Borges de; Jr., Paulo Souza Müller; Oliveira, Danielle Fernanda de Melo; França, Marcela Dias (IntechOpen, 2012)
None